Efek Sinergis dan Antagonis Campuran Herbisisda Metolachlor dan Pendimethalin di Pertanaman Kedelai (Glycine max L. Merril) - Baidhawi Baidhawi (Jurnal Agrista, 2006)
Effect of Sinergism and Antagonism Mix of Herbicide Metolachlor and Pendimethalin in Soybean (Glycine max L. Merril) AreaABSTRACT. The mixture two or more herbicide are represent to anticipate weakness in use herbicide at one particular crop specially in soybean. Research was aimed to find out influence of mixture two herbicide, with under various dosage to weeds and yield of soybean. Field research was conducted from February 2006 until May 2006 at station research Agriculture faculty Padjajaran University. The factorial experiment was carried out in randomized completely block design. The two factors are Metolachlor and Pendimethalin. Our result the mixture metolachlor and pendimethalin showed synergistic and antagonistic effect to population and weeds dried matter by used Colby’s method, however with used regression method, the population of weeds showed effect synergistic, and weeds dried matter not showed effect synergistic. The mixture metolachlor and pendimethalin can increased dried yield with compared to applied single doses.